Improving Training of Modern Leaders Utilizing it in The Administration of The Higher Education System - Suyunovich, Temirov Ortiq; Fayzievna, Hakimova Muhabbat (Universitas Pendidikan Indonesia (UPI), 2023)
This paper aims to discuss the problem of organizing students ' independent educational activities using IT projects and task management system. The concept of